Rapid Regulation of Alternative Splicing in Response to Environmental Stresses - Liu, Xiao-Xiao; Guo, Qian-Huan; Xu, Wei-Bo; Liu, Peng; Yan, Kang (Frontiers in Plant Science, 2022)
Plants overcome the changing environmental conditions through diverse strategies and complex regulations. In addition to direct regulation of gene transcription, the Alternative Splicing (AS) also acts as a crucial regulatory mechanism to cope with various stresses. Generating from the same pre-mRNA, AS events allow rapid adjustment of the abundance and function of key stress-response components. Mounting evidence has indicated the close link between the AS and plant stress response. However, the mechanisms on how environmental stresses trigger AS are far from understood. The advancing high-throughput sequencing technologies have been providing useful information, whereas the genetic approaches have also yielded remarkable phenotypic evidence for AS control of stress responses. It is important to study how stresses trigger AS events for both fundamental science and applications. We review current understanding of stress-responsive AS in plants and discuss research challenges for the near future, including regulation of splicing factors, epigenetic modifications, the shared targets of splice isoforms, and the stress-adjusting ratios between splicing variants.